PENGARUH POLA PENGAJARAN KOMUNIKASI DIADIK DAN POLA PENGAJARAN INTERAKSI EDUKATIF TERHADAP HASIL BELAJAR MAHASISWA PENDIDIKAN AKUNTANSI FKIP UNIVERSITAS PGRI PALEMBANG - Lestari, Neta Dian (RIPTEKSI KEPENDIDIKAN PGRI, 2013)
AbstractThe results of the data analysis there is a correlation between the pattern of dyadic communication teaching on learning outcomes of accounting students at the University of PGRI Palembang for 0.066 and there is a correlation between the pattern of teaching educational interaction on learning outcomes of accounting students at the University of PGRI Palembang at 0. 436. Multiple correlation is also a correlation between the pattern of teaching dyadic communication and interaction patterns educative teaching to student learning outcomes at the University of PGRI Palembang for 0.476. R Square of 0:39, meaning 39% of accounting student learning outcomes described by variable patterns of dyadic communication teaching and variable patterns of teaching educational interaction, while the rest can be explained by other factors not examined in this research model. The regression equation was obtained: Y = 59.402 + 0.100X1 + 0.527 X2 + e.It can be concluded that: 1). There is the influence of dyadic communication patterns of teaching on learning outcomes of accounting students at the University of PGRI Palembang, 2). There is the influence of educational interaction pattern of teaching on learning outcomes of accounting students at the University of PGRI Palembang, 3). There is the influence of dyadic communication patterns of teaching, educational interaction patterns of teaching on learning outcomes of accounting students at the University of PGRI Palembang.Â Keywords : dyadic communication, education interaction andlearning outcomes of accounting students.